A prospective observational study of post-partum intrauterine contraceptive device acceptance in a tertiary care centre - Bavdekar, Nitin; Lewis, Preeti F.; Sanjay Gupta, Shusmita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Provision of PPIUCD is being rapidly scaled up in India with facilities in at least 19 states offering the method in 2013. According to National Family Health Survey (NFHS)-3, the prevalence of modern method of contraceptive use is 48.5% and all methods 56% in India. PPIUCD placement remains a viable option for patients who wish to use a long-acting reversible contraceptive (LARC) method and to have it placed at the time of their delivery. Hence, we planned this study with an aim to evaluate acceptability PPIUCD at tertiary care centre. Methods: It was an observational and prospective study of acceptance of PPIUCD as a method of contraception in patients who delivered within the study period in our institute Grant Medical Hospital and College, Mumbai. Data analysis was done with statistical software SPSS V 25.0. Results: A total of 2014 patients were enrolled in the study. The mean age was noted to be 25.87 years. Frequency of ANC visits among the patients was 4 to 6 (39.87%). Commonest obstetric history finding was previous live birth history in 59.38% cases. Pregnancy outcome was vaginal delivery noted in 63.01% of the females. 879 (43.65%) cases accepted PPIUCD. For those who did not accept PPIUCD, commonest cause was tubal ligation in 34.19%, followed by fear of pain in 18.94%, partner’s refusal in 10.31%. Conclusions: The acceptance rate in study for PPIUCD was 43.65% which was higher than most of the published evidence. The common reasons for not accepting PPIUCD were tubal ligation.